Oh honey, that's an easy one. Two sixths plus one sixth equals three sixths. And if you want to simplify it, three sixths is the same as one half. So there you have it, simple math for a simple question.
One half = three sixth, so the answer is two sixth.
it equals five sixth.
one-sixth
well three-sixth-two-sixth is one-sixth
one and two sixth's
Four and one sixth.
Oh honey, that's an easy one. Two sixths plus one sixth equals three sixths. And if you want to simplify it, three sixths is the same as one half. So there you have it, simple math for a simple question.
seven sixths so 1whole and a sixth
It is: 10
1 third plus one third =============== There are many other fraction combinations which equal two-thirds. One, for example, is one-half plus one-sixth.
One half = three sixth, so the answer is two sixth.
Well, isn't that a happy little math question! When you add one-third and one-sixth together, you can simplify it by finding a common denominator, which is six. So, one-third is equal to two-sixths. When you add two-sixths and one-sixth together, you get three-sixths, which simplifies to one-half. Isn't that just lovely?
2/3 + 1/2 = 1 1/6 or one and one sixth.
it equals five sixth.
one half
Nine and five sixth